2005
DOI: 10.1073/pnas.0406382102
|View full text |Cite
|
Sign up to set email alerts
|

Role of SDF1 chemokine in the development of lateral line efferent and facial motor neurons

Abstract: Most sensory systems are innervated by efferent neurons as well as by afferent neurons. The efferent innervation modulates the sensitivity of the receptor cells or of the sensory terminals. In the posterior lateral line system of the zebrafish, two efferent nuclei have been described in the hindbrain. Here we examine the development of the efferent neurons. We show that their axons are guided toward the target organ along the lateral line nerve while their cell bodies migrate posteriorward across rhombomeres t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
2
49
0
Order By: Relevance
“…Recent studies demonstrated that inactivation of CXCL12 and CXCR4 prevents PLL primordium migration, resulting in the formation of defective PLL (David NB et al, 2002;Li Q et al, 2004;Haas P and Gilmour D, 2006). The migration of motor neurons of the facial nucleus from rhombomere 4 to 6 was also affected in CXCL12 morphants (Sapede D et al, 2005). In CXCR4 mutant mice, the number of muscle progenitors that colonized the anlage of the tongue and the dorsal limb was reduced.…”
Section: Others-cxcl12/cxcr4mentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies demonstrated that inactivation of CXCL12 and CXCR4 prevents PLL primordium migration, resulting in the formation of defective PLL (David NB et al, 2002;Li Q et al, 2004;Haas P and Gilmour D, 2006). The migration of motor neurons of the facial nucleus from rhombomere 4 to 6 was also affected in CXCL12 morphants (Sapede D et al, 2005). In CXCR4 mutant mice, the number of muscle progenitors that colonized the anlage of the tongue and the dorsal limb was reduced.…”
Section: Others-cxcl12/cxcr4mentioning
confidence: 97%
“…In zebrafish, peripheral sensory efferent projection requires intact CXCL12/CXCR4 signaling (Gilmour D et al, 2004;Sapede D et al, 2005). The peripheral PLL in zebrafish receives axonal afferent inputs from two different efferent nuclei in the hindbrain (Metcalfe WK et al, 1985).…”
Section: Axon Guidance and Pathfindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The 26-1 mutation is in neither of these genes. Although chemokines and their receptors have been shown to direct cell migration in the nervous system (Bagri et al, 2002;Lu et al, 2002;Stumm et al, 2003;Belmadani et al, 2005;Knaut et al, 2005;Miller and Tran, 2005;Sapede et al, 2005), so far none has been shown to affect telencephalic patterning. Nonetheless, it is attractive to speculate that 26-1 affects a gene with a key role in directing motor axon outgrowth by affecting the SDF1(Cxcl12)-Cxcr4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hedgehog proteins are modified by cholesterol (for a review, see Bürglin, 2008;Porter et al, 1996). It is also likely that the disruption of other heterotrimeric G-protein-dependent signaling pathways, including Sdf1 (Cxcl12)/Cxcr4 (Sapède et al, 2005;Cubedo et al, 2009), contributes to FBMN migration defects in Pggt1b-deficient embryos. Finally, the disrupted geranylgeranylation of small GTPases might cause cytoskeletal disorganization and further impair migration.…”
Section: Discussionmentioning
confidence: 99%